Price convergence and geographic dimension of market integration: Evidence from China - Maria Ritola (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
This study analyses the level and geographic dimension of China's market integration. The objective is to provide a broad characterization of China's market integration by performing a variety of empirical tests and providing comparisons to other studies on the same topic. The models tested are grounded in the law of one price. Price convergence is analysed with univariate time series methods, where linear and non-linear cointegration models refer to convergence in the short run and in the long run, respectively. The non-linear model is considered a good fit for analysing transitional economies, because the non-linear trend variable in the model indicates whether there is movement towards integration in the long run. Convergence of prices is first analysed by comparing city-level prices with China's national average price level and then by dividing China into three regional clusters. The estimation results suggest that the level of integration across Chinese cities is fairly high by international standards. The great majority of price series trending towards integration are services. The geographic pattern of China's market integration did not turn out as expected. Eastern cities are among the least integrated cities in the nationwide examination. Relatively high levels of integration were detected from several central and south-eastern cities. Furthermore, the cluster convergence approach to analyse China's market integration did not augment the eastern cities' level of convergence.
URN:NBN:fi:bof-201408072153
Keywords: 330